2010
DOI: 10.1002/ptr.3129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of furostanol glycosides from Trigonella foenum‐graecum on the reproductive system of male albino rats

Abstract: Trigonella foenum (TF) has long been used in the traditional Indian systems of medicine for the treatment of various ailments. The objective was to study the anabolic and androgenic activity of the furostanol glycosides fraction of Trigonella foenum-graecum (Fenu-FG) in immature castrated male Wistar rats. It was also aimed to investigate the effect of Fenu-FG on testicular histology in non-castrated immature rats. The animals (55 ± 5 g) were castrated. The rats were treated with either vehicle, testosterone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Chinese traditional medicine system has also reported the tonic property of fenugreek seed for the treatment of weakness and edema of the legs [17] as well as reproductive property [18]. Furostanol glycosides isolated from fenugreek seed possess anabolic and androgenic activity in laboratory rats [19]. The extraction, characterization and toxicological studies of glycosides based standardized fenugreek seed extract (SFSE-G) has been reported recently [20].…”
Section: Introductionmentioning
confidence: 98%
“…Chinese traditional medicine system has also reported the tonic property of fenugreek seed for the treatment of weakness and edema of the legs [17] as well as reproductive property [18]. Furostanol glycosides isolated from fenugreek seed possess anabolic and androgenic activity in laboratory rats [19]. The extraction, characterization and toxicological studies of glycosides based standardized fenugreek seed extract (SFSE-G) has been reported recently [20].…”
Section: Introductionmentioning
confidence: 98%
“…An animal study by Hamden et al [25] found that daily oral treatment of fenugreek steroids to diabetic rats over 30 days induced a considerable increase in testosterone in the plasma of the rats. However, a clinical study by Steels et al [8] and an animal study using male albino rats conducted by Aswar et al [26] did not reveal significant changes in testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, Aswar et al [26] reported that Trigonella foenum-graecum increased the weight of the levator ani muscle, as well as the body weight of castrated rats. They suggested that Trigonella foenum-graecum has anabolic properties (increasing muscle mass), and that the probable mechanism for this action is increased availability of testosterone by dissociating it from the stored form, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another research group, Mozaffari et al (2010) highlighted that, fenugreek treatment (3.2 g/kg) to pregnant rats caused severe adverse alterations in rat fetus such as disorder in developing hind limb long bone. However, Aswar et al (2010) have reported that furostanol glycosides fraction of fenugreek did not change testosterone level and angrogenic activity in rats.…”
Section: Introductionmentioning
confidence: 90%